APC mutation and tumour budding in colorectal cancer. Issue 1 (1st January 2003) - Jass, J R; Barker, M; Fraser, L; Walsh, M D; Whitehall, V L J; Gabrielli, B; Young, J; Leggett, B A
Abstract : Aim: To determine the frequency of tumour budding and somatic APC mutation in a series of colorectal cancers stratified according to DNA microsatellite instability (MSI) status. Material/Methods: Ninety five colorectal cancers were genotyped for APC mutation in the mutation cluster region (exon 15) and scored for the presence of tumour budding at the invasive margin in haematoxylin and eosin stained sections. A subset was immunostained for β catenin and p16. Results: The frequency of both somatic APC mutation and tumour budding increased pari passu in cancers stratified as sporadic MSI high (MSI-H), hereditary non-polyposis colorectal cancer (HNPCC), MSI low (MSI-L), and microsatellite stable (MSS). Both budding and APC mutation were significantly less frequent in sporadic MSI-H cancers than in MSI-L or MSS cancers. Tumour buds were characterised by increased immunostaining for both β catenin and p16. Conclusion: Tumour budding is associated with an adverse prognosis. The lack of budding in MSI-H colorectal cancer may account for the improved prognosis of this subset and may be explained by an intact WNT signalling pathway and/or inactivated p16 INK4a .